Preparation of high-temperature-resistant and high-strength low-density oil well cement. Issue 1 (11th February 2020) - Tian, Yong; Yu, Rangang; Zhang, Neng; Yang, Yingtao
Abstract : Heavy-oil thermal recovery wells and ultradeep-well cementing have high requirements for the high-temperature compressive strength and density of oil well cement. In this research, experimental studies on the influence of quartz powder content and particle size on the compressive strength of oil well cement stone were carried out under different temperatures. The test results showed that the strength of oil well cement decreased with the increase in the particle size of quartz powder at the same temperature conditions. This provided a basis for further selection and design of a high-temperature-resistant and low-density slurry cementing system. The compressive strength of the cement stone was improved by adding a water-reducing agent in proportion A. On this basis, a kind of high-strength, high-temperature-resistant and low-density well cementing slurry was prepared by substituting microsilica for quartz powder in proportion B and adding a water-reducing agent at the same time. The thermal conductivity of this cement stone was only 0·55 (W/m)/K; therefore, the temperature stress produced by too large temperature rising of the casing can be avoided to a certain extent. Formula B can meet the hot-mining cementing requirements of a stratum with a very low fracture pressure.